2020
DOI: 10.1002/pip.3350
|View full text |Cite
|
Sign up to set email alerts
|

WS2 and MoS2 counter electrode materials for dye‐sensitized solar cells

Abstract: Being confronted with the energy crisis and environmental problems, the exploration of clean and renewable energy materials as well as their devices are urgently demanded. Dye‐sensitized solar cells (DSSCs) have attracted widespread attention in recent years as potential cost‐effective alternatives to silicon‐based and thin film solar cells. Two‐dimensional (2D) graphene‐like transition metal dichalcogenides (TMDs), such as WS2 and MoS2, have showed vast potential as novel energy materials due to their unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 216 publications
0
20
0
Order By: Relevance
“…834 CV measurements revealed that both MoS 2 -and WS 2 -based CEs hold a catalytic activity, for the redox couple regeneration, comparable to that of the Pt-based CE. 833 Consequently, the DSSCs using MoS 2 -and WS 2 -based CEs have shown an Z value of 7.59% and 7.73%, respectively, which were comparable to that of the reference DSSC using a Pt-based CE. 833 EIS analysis estimated R CT values of 0.5 and 0.3 O for MoS 2 -and WS 2 -based CE, respectively, together with large electrode capacitances (134 and 198 mF, respectively) (i.e., large SSA).…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…834 CV measurements revealed that both MoS 2 -and WS 2 -based CEs hold a catalytic activity, for the redox couple regeneration, comparable to that of the Pt-based CE. 833 Consequently, the DSSCs using MoS 2 -and WS 2 -based CEs have shown an Z value of 7.59% and 7.73%, respectively, which were comparable to that of the reference DSSC using a Pt-based CE. 833 EIS analysis estimated R CT values of 0.5 and 0.3 O for MoS 2 -and WS 2 -based CE, respectively, together with large electrode capacitances (134 and 198 mF, respectively) (i.e., large SSA).…”
mentioning
confidence: 59%
“…833 Consequently, the DSSCs using MoS 2 -and WS 2 -based CEs have shown an Z value of 7.59% and 7.73%, respectively, which were comparable to that of the reference DSSC using a Pt-based CE. 833 EIS analysis estimated R CT values of 0.5 and 0.3 O for MoS 2 -and WS 2 -based CE, respectively, together with large electrode capacitances (134 and 198 mF, respectively) (i.e., large SSA). 833 These values outperformed those of Pt-based CE (R CT of 3 O and capacitance of 2.1 mF).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Recently, the high catalytic activity of the CE toward the reduction of I 3 − has become an important research area because the CE executes two important tasks: it catalyzes the reduction reaction of the electrolyte (I 3 − to I − ) and also collects the electrons from the external circuit carrying them back to the dye. [ 90 ] CEs are commonly made of a thin film of Pt and although its performance is very efficient, its high cost restricts further development. Therefore, to develop alternative and cheaper materials to substitute Pt electrodes has become a priority.…”
Section: Applications Of Phase‐engineered 2d Tmds Prepared By Cvdmentioning
confidence: 99%